The role of ICT infrastructure on Malaysian trade - Ahmad, Nor Asma; Ismail, Normaz Wana; Law, Siong Hook (Faculty of Economics and Management, Universiti Putra Malaysia, 2011)
This paper examines the impact of ICT infrastructure on trade in the case of Malaysia by using a gravity model and a number of indicators for the ICT infrastructure. The analyses are based on panel data 36 trading partner countries from 1980 to 2008. It is found that mobile and fixed-line telephone subscribers, personal computers and internet users are significant and positively related to the value of bilateral trade between Malaysia and its trading partners. The results support that ICT infrastructure development serves as the key facilitating role in achieving higher levels of exports in Malaysia.